2021
DOI: 10.3389/fpsyt.2021.759694
|View full text |Cite
|
Sign up to set email alerts
|

Physical Health Profile and Associated Behavior During the COVID-19 Pandemic in Patients With Bipolar Disorder

Abstract: Background: The COVID-19 pandemic has led to an increased psychological strain on public mental health and may impact behavioral, mental, and physical health, presumably with effects on patients with severe mental disorders. This study examines pandemic-related physical and mental health and (compensatory) behavioral changes, in patients with BD as compared to healthy control individuals.Method: Physical and mental health and self-reported changes in daily structure and behavior due to the pandemic were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…A recent study by Solè et al ( 2021 ), investigating the effects of COVID-19 pandemic effects, showed that people with severe mental illness reported weight gain and sleep disturbances during lockdown. A decrease in physical activity during the first wave of COVID-19 in people with bipolar disorder compared to healthy controls was also reported by Sperling et al, ( 2021 ).…”
Section: Discussionsupporting
confidence: 75%
“…A recent study by Solè et al ( 2021 ), investigating the effects of COVID-19 pandemic effects, showed that people with severe mental illness reported weight gain and sleep disturbances during lockdown. A decrease in physical activity during the first wave of COVID-19 in people with bipolar disorder compared to healthy controls was also reported by Sperling et al, ( 2021 ).…”
Section: Discussionsupporting
confidence: 75%
“…In line with this data, the results of a recent study carried out during the pandemic in patients with mental disorders found a higher body mass index compared to the general population. Furthermore, participants with mental disorders more frequently reported weight gain > 5 kg during the pandemic [ 43 ]. In addition, some authors have observed that a high BMI is a risk factor for the development of critical conditions in patients infected with SARS-CoV-2 [ 44 ], thereby representing an added risk in the population with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of a large-scale study examining several other variables and overlapped with two other studies based on the baseline result [34,35]. These studies showed that the pandemic had a greater impact on the physical health of individuals with BD, in comparison to HC [35] and that emotional distress due to social distancing was related to more clinical symptoms (e.g., somatization, sleep quality) in individuals with BD than HC [34]. All questionnaires were administered in German (for Austria and Germany) or Danish.…”
Section: Methodsmentioning
confidence: 99%